Diversity of Butterflies (Lepidoptera) in the Bonsai Park, Tapan Village, Kedungwaru District, Tulungagung Regency - Urmila Yuniska Nuraini; Hamidha Septa Maharani (Jurnal Pijar MIPA, 2026)
Butterflies are insects that can inhabit various types of habitats, but differences in habitat conditions may influence their abundance and species diversity. Bonsai Park, located in Tapan Village, Kedungwaru District, Tulungagung Regency, East Java, is a tourist area with vegetation that potentially supports butterfly populations. However, scientific information on butterfly diversity in this area remains limited. The lack of such data may hinder efforts to understand local biodiversity conditions and opportunities for pollinator conservation. Therefore, this study aimed to identify butterfly species and analyze their diversity and relative abundance in Bonsai Park, Tapan Village. This research employed a quantitative descriptive approach using the transect method. Sampling was conducted along three transect lines, each approximately 100 m in length, with an observation width of about 5 m on both sides of the transect. Sampling was carried out between 08.00–11.00 WIB using an insect net with the sweeping technique. Sampling was repeated four times at weekly intervals during the research period. Data analysis included the Shannon–Wiener diversity index (H’) and relative abundance. The results showed that 7 butterfly species, totalling 21 individuals, were recorded, belonging to 4 families: Nymphalidae, Lycaenidae, Pieridae, and Papilionidae. The identified species were Euploea crameri, Junonia atlites, Acraea terpsicore, Danaus chrysippus, Tajuria cippus, Leptosia nina, and Papilio demoleus. The Shannon–Wiener diversity index (H’) value of 1.746 indicates a moderate level of diversity, with the highest abundance found in Junonia atlites. These findings suggest that Bonsai Park can still support several butterfly species as part of local biodiversity. Ecological management strategies, such as planting host plants for larvae, increasing the number of flowering plants as nectar sources, and enhancing vegetation heterogeneity, are recommended to improve habitat quality and support butterfly conservation in the area.